2016
DOI: 10.1093/nar/gkw1149
|View full text |Cite
|
Sign up to set email alerts
|

Yeast DNA polymerase ζ maintains consistent activity and mutagenicity across a wide range of physiological dNTP concentrations

Abstract: In yeast, dNTP pools expand drastically during DNA damage response. We show that similar dNTP elevation occurs in strains, in which intrinsic replisome defects promote the participation of error-prone DNA polymerase ζ (Polζ) in replication of undamaged DNA. To understand the significance of dNTP pools increase for Polζ function, we studied the activity and fidelity of four-subunit Polζ (Polζ4) and Polζ4-Rev1 (Polζ5) complexes in vitro at ‘normal S-phase’ and ‘damage-response’ dNTP concentrations. The presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 86 publications
0
21
0
Order By: Relevance
“…Such analysis of mutation specificity should reveal whether the elimination of the Rev3p‐Pol31p interaction, thus lack of Pol ζ 4 , leads to the disappearance of some features attributable to Pol ζ. As shown by a recent in vitro study, base substitutions, most frequently G→T, predominate in Pol ζ 4 spectra and also a noticeable number of complex mutations is observed (Kochenova et al ., ). Additionally, a significant increase in the rates of X‐dCTP mispairs is observed in spectra of Pol ζ 5 (stoichiometric Rev3p, Rev7p, Pol31p, Pol32p and Rev1p complex), apparently as a result of Rev1p deoxycytidyl‐transferase activity (Kochenova et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Such analysis of mutation specificity should reveal whether the elimination of the Rev3p‐Pol31p interaction, thus lack of Pol ζ 4 , leads to the disappearance of some features attributable to Pol ζ. As shown by a recent in vitro study, base substitutions, most frequently G→T, predominate in Pol ζ 4 spectra and also a noticeable number of complex mutations is observed (Kochenova et al ., ). Additionally, a significant increase in the rates of X‐dCTP mispairs is observed in spectra of Pol ζ 5 (stoichiometric Rev3p, Rev7p, Pol31p, Pol32p and Rev1p complex), apparently as a result of Rev1p deoxycytidyl‐transferase activity (Kochenova et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…As shown by a recent in vitro study, base substitutions, most frequently G→T, predominate in Pol ζ 4 spectra and also a noticeable number of complex mutations is observed (Kochenova et al ., ). Additionally, a significant increase in the rates of X‐dCTP mispairs is observed in spectra of Pol ζ 5 (stoichiometric Rev3p, Rev7p, Pol31p, Pol32p and Rev1p complex), apparently as a result of Rev1p deoxycytidyl‐transferase activity (Kochenova et al ., ). These results are consistent with previous in vivo studies in which complex mutations and GC→CG transversions were considered as hallmarks of Pol ζ‐dependent mutagenesis (Harfe and Jinks‐Robertson, ; Kraszewska et al ., ; Grabowska et al ., ; Northam et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…We have previously shown that Pol z can be purified as a stable 5-subunit complex together with Rev1 (36). A complex with the identical activity can also be obtained by simply mixing Pol z together with Rev1, thereby reconstituting the 5-subunit complex.…”
Section: In Vitro Bypass Of An Icl By Pol H and Rev1-pol Zmentioning
confidence: 99%
“…The reaction was started by addition of the individual DNA polymerases. dNTPs were present at concentrations that prevail during the DNA damage response in yeast (36). Replication of the undamaged control DNA was carried out very efficiently, with the exception of replication by Rev1-Pol z (lane 5, discussed below).…”
Section: In Vitro Bypass Of An Icl By Pol H and Rev1-pol Zmentioning
confidence: 99%
See 1 more Smart Citation